2020
DOI: 10.1371/journal.pone.0235834
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between internet use, deliberate self-harm, and happiness in adolescents: A Taiwan birth cohort pilot study

Abstract: The potential risk of internet use on adolescents' self-harm is a major concern. Vulnerable adolescents who are susceptible to bullying are also susceptible to the negative influence of the internet. In this study, the pathway associations were investigated between the risk factors of deliberate self-harm, experience of being bullied, internet use, and protective factors of maternal monitoring on perceived happiness of 12-and 13-year-old adolescents in the Taiwan Birth Cohort Pilot Study dataset (n = 1,457). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
2
17
0
5
Order By: Relevance
“…Our large national birth cohort study showed that those with higher absorptive dissociative trait, lower parental monitoring, and who have been bullied in school were more likely to spend more than five hours online during school days and expressed higher depressed mood and a lower level of perceived happiness. This result is in line with the Taiwan Birth Cohort pilot study (n = 1457), which found that adolescents who spend more than five hours online have an increased risk of deliberate self-harm and a lower level of happiness [24], showing that spending more than five hours online per day may be a clinical prevention indicator for problematic internet use. Since parental monitoring is a protective factor for internet addiction, parents should provide monitoring and guidance while respecting the autonomy of adolescents, thereby reducing the motivation of adolescents to become involved with social networking and risks for internet addiction [19,36].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our large national birth cohort study showed that those with higher absorptive dissociative trait, lower parental monitoring, and who have been bullied in school were more likely to spend more than five hours online during school days and expressed higher depressed mood and a lower level of perceived happiness. This result is in line with the Taiwan Birth Cohort pilot study (n = 1457), which found that adolescents who spend more than five hours online have an increased risk of deliberate self-harm and a lower level of happiness [24], showing that spending more than five hours online per day may be a clinical prevention indicator for problematic internet use. Since parental monitoring is a protective factor for internet addiction, parents should provide monitoring and guidance while respecting the autonomy of adolescents, thereby reducing the motivation of adolescents to become involved with social networking and risks for internet addiction [19,36].…”
Section: Discussionsupporting
confidence: 87%
“…Twenge, Joiner, Rogers, and Martin found that adolescents who spent more time on new media screen activities (such as smartphone devices and social media) were more likely to report mental health issues, and those who reported to have spent more time on non-screen activities (such as exercise or in-person interaction) were less likely to report mental health issues [8]. Furthermore, the Taiwan Birth Cohort pilot study found that 12-year-old adolescents who spend more than five hours online during days without school were at a higher risk of deliberate self-harm at thirteen, as well as a perceived lower level of happiness [24]. The negative relationship between internet use and exercise was also found in our study; adolescents that spent more time online were less likely to exercise regularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluations of ‘screen time’ indicate that Chinese adolescents spend 7.56 hours/day on viewing screens, American adolescents spend 7.22 hours/day and Australians adolescents spend 6.23 hours/day [ 1 – 3 ]. While the use of the internet by adolescents can be beneficial, the ‘problematic’ use of the internet has also been shown to affect academic performance [ 4 ], subjective wellbeing [ 5 ], anxiety [ 6 ], depressive symptoms [ 7 ], sleep disorders [ 8 ], reduced leisure activities [ 9 ], obesity [ 10 ], and suicidality [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em Taiwan, estudos que buscaram fazer relações entre o vício da Internet e automutilação deliberada entre adolescentes identificaram que os sujeitos que passaram mais de cinco horas online durante os dias de folga da escola apresentaram maior risco de automutilação relacionada Cyberbullying e mostraram um nível mais baixo de felicidade e autoestima (Lung et al, 2020).…”
Section: Internet E O Contágio Socialunclassified